2016
DOI: 10.1063/1.4959891
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous properties and the liquid-liquid phase transition in gallium

Abstract: A group of materials including water and silicon exhibit many anomalous behaviors, e.g., density anomaly and diffusivity anomaly (increase upon compression). These materials are hypothesized to have a liquid-liquid phase transition (LLPT) and the critical fluctuation in the vicinity of the liquid-liquid critical point is considered as the origin of different anomalies. Liquid gallium was also reported to have a LLPT, yet whether it shows similar water-like anomalies is not yet studied. Using molecular dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…It was found that the tri-layer structure is thermodynamically stable to 306 K higher than the bi-layer structure. 24 Furthermore, studies centering around the liquid phase of bulk Ga have shown liquid-liquid phase transitions, [31][32][33][34][35] a tri-layered liquid structure at the free surface 36 and structural ordering at high pressure and temperature. 37 Ordering in 2D liquid phases has a long history.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the tri-layer structure is thermodynamically stable to 306 K higher than the bi-layer structure. 24 Furthermore, studies centering around the liquid phase of bulk Ga have shown liquid-liquid phase transitions, [31][32][33][34][35] a tri-layered liquid structure at the free surface 36 and structural ordering at high pressure and temperature. 37 Ordering in 2D liquid phases has a long history.…”
Section: Introductionmentioning
confidence: 99%
“…A few substances in nature display anomalous density changes, e.g., their density decreases upon transition from liquid to solid. Such anomalous density change may originate either from directional intermolecular hydrogen bonds, e.g., in the case of liquid water 1 , or from directional covalent bonds, e.g., in cases of liquid phosphorus 2 , gallium 3 , and silicon 4 , 5 . For two-dimensional (2D) matter, e.g., liquid water confined to a nano-slit, a similar anomalous first-order transition between the high-density liquid and low-density amorphous ice has been predicted based on atomistic molecular simulations 1 .…”
Section: Introductionmentioning
confidence: 99%
“…An example of the theoretical approaches used to look at this problem are models for the structure of liquid alloys such as those developed in [7,8]. The possible existence of a liquid-liquid phase transition has been an issue for several investigations [9][10][11][12][13][14][15]. However, systematic experimental investigations in terms of composition, temperature and time dependencies of the physical properties of molten alloys have not been performed.…”
Section: Introductionmentioning
confidence: 99%